2013
DOI: 10.4028/www.scientific.net/msf.745-746.734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe on Crystallization Process of Zr-Co-Al-(Fe) Bulk Metallic Glasses

Abstract: The change in the internal states of Zr56Co28Al16 bulk metallic glass (BMG) upon minor substitution of Co with Fe was investigated for alloys with different compositions of Zr56Co28-xAl16Fex (x = 0, 1 and 2, respectively). Results exhibited that the ductile Zr-Co-Al-Fe BMGs were obtained and showed better glass-forming ability (GFA) via a small amount of Co partial replacement by Fe. In addition, the addition of a small amount of Fe enhanced the crystallization process and reduced the activation energy. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…As reported in the literature, it concerns ternary alloys such as CuZrPd [47], AlNiCo [48], CuZrAl [49,50], and AlNiLa [51]. Several studies have achieved devitrification in multicomponent amorphous systems in supercooling condition, namely ZrCoAlFe [52], LaAlNiCu [53], Zr-TiNiCuBe [54,55], and ZrTiCuNiAl [56]. The authors support that the atomic element size and the stoichiometry of mixtures are fundamental ingredients to realize devitrification.…”
Section: Introductionsupporting
confidence: 53%
“…As reported in the literature, it concerns ternary alloys such as CuZrPd [47], AlNiCo [48], CuZrAl [49,50], and AlNiLa [51]. Several studies have achieved devitrification in multicomponent amorphous systems in supercooling condition, namely ZrCoAlFe [52], LaAlNiCu [53], Zr-TiNiCuBe [54,55], and ZrTiCuNiAl [56]. The authors support that the atomic element size and the stoichiometry of mixtures are fundamental ingredients to realize devitrification.…”
Section: Introductionsupporting
confidence: 53%
“…Furthermore, minor addition of Ag or Fe can significantly improve the GFA of Zr-Co-Al system. [25][26][27] Moreover, it was reported that increasing Ni/Fe concentration ratio can effectively improve the compressive plasticity in Fe-Ni-Nb-B bulk glassy alloys [28]. The Al content can affect the formation and the mechanical properties in CuZr-based BMGs and their composites.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, in BMGs with a maximum nucleation and the minimum growth rates, crystallization process can take place partially by controlling the kinetic parameters and as a result an amorphous matrix nanocomposite can be produced with excellent mechanical and magnetic properties [ 27 , 28 , 29 ]. On the other hand, the presence of alloying elements can strongly control the size of crystalline particles during annealing process [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. For instance, Lesz et al [ 32 ] studied the effect of Ni addition on the thermal properties of a Fe-based amorphous alloy.…”
Section: Introductionmentioning
confidence: 99%